2011
DOI: 10.1002/hed.21654
|View full text |Cite
|
Sign up to set email alerts
|

Factors predictive of severity of osteoradionecrosis of the mandible

Abstract: The above-cited factors are predictive of severity and can potentially guide prophylaxis and management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
24
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 19 publications
6
24
4
Order By: Relevance
“…The sample size (153 cases) is much higher compared with some of the previous studies (Chopra et al, 2011, Gevorgyan et al, 2013. The retrospective design of the study introduced some limitations.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The sample size (153 cases) is much higher compared with some of the previous studies (Chopra et al, 2011, Gevorgyan et al, 2013. The retrospective design of the study introduced some limitations.…”
Section: Discussionmentioning
confidence: 82%
“…The majority of studies dealing with ORN have focused on risk factors associated with the causation of ORN (Morrish et al, 1981, Kluth et al, 1988, Jereczek-Fossa and Orecchia, 2002, Reuther et al, 2003, Gomez et al, 2011, Niewald et al, 2013, Tsai et al, 2013. To our knowledge, only four studies were found dealing with the severity of ORN (Store and Boysen, 2000, Notani , Chopra et al, 2011, Gevorgyan et al, 2013. They either consisted of a small sample size (Gevorgyan et al, 2013) or focused on the severity of ORN proposing new classification systems or modalities of therapy (Store andBoysen, 2000, Notani et al, 2003).…”
Section: Discussionmentioning
confidence: 94%
“…The primary factor implicated in the pathogenesis of ORN is the amount of radiation given to the affected bone, with both early (Ͻ2 years from radiation) and late onset ORN (Ͼ2 years from radiation) seen. 4 There is a wide range of incidence of mandibular ORN reported, ranging from 5% to 22%, with more recent studies showing a decreased incidence, presumably attributable to increasing awareness and to improvements in preventive care and radiation techniques. [5][6][7][8][9] Patients are often referred for imaging to evaluate the extent of clinically suspected ORN, and, at the same time, to assess potential tumor recurrence.…”
mentioning
confidence: 99%
“…Some studies have shown that the lack of pre-radiotherapy extractions presents a risk factor for ORN [28], while other studies have found that preradiotherapy extractions are not beneficial in reducing rates of ORN regardless of tooth condition [20] and may actually increase the overall risk of ORN [4,18,21,22]. 20 If extractions are performed, it is important to allow sufficient healing time prior to the commencement of radiotherapy but not to unduly delay it.…”
Section: Pre-radiotherapy Dental Management: Extractionsmentioning
confidence: 99%
“…The authors do not encourage use of antibiotics where there is no infection. 28 Autologous PRP has been promoted for various applications, including bone grafts and various head and neck procedures. The theoretical mechanism of prophylaxis is that a number of growth factors present in platelets, including PDGF, TGFβ and VEGF, result in improved healing and better outcomes.…”
Section: Post-radiotherapy Management: Orn Antibiotics and Prpmentioning
confidence: 99%